Lares (1868) - Todd, Roberto H. (My University, 2015)
Artículo relacionado al Grito de Lares.
Keywords: Ramírez, Francisco; Acosta y Calbo, José Julián de, 1825-1891; Mariano Quiñones, Francisco, 1830-1908; Puerto Rico--History--Insurrection, 1868.; Ruiz Belvis, Segundo, 1829-1867; Rojas, Manuel